Ethical guidelines for publishing in the Journal of Cachexia, Sarcopenia and Muscle: update 2021. Issue 6 (13th December 2021) - von Haehling, Stephan; Coats, Andrew J.S.; Anker, Stefan D.
Abstract: The Journal of Cachexia, Sarcopenia and Muscle (JCSM) aims to publish articles with relevance to wasting disorders and illnesses of the muscle in the broadest sense. In order to avoid publication of inappropriate articles and to avoid protracted disputes, the Editors have established ethical guidelines that detail a number of regulations to be fulfilled prior to submission to the journal. This article updates the principles of ethical authorship and publishing in JCSM and its two daughter journals JCSM Rapid Communication and JCSM Clinical Reports . We require the corresponding author, on behalf of all co‐authors, to certify adherence to the following principles: All authors listed on a manuscript considered for publication have approved its submission and (if accepted) approve publication in the journal; Each named author has made a material and independent contribution to the work submitted for publication; No person who has a right to be recognized as author has been omitted from the list of authors on the submitted manuscript; The submitted work is original and is neither under consideration elsewhere nor that it has been published previously in whole or in part other than in abstract form; All authors certify that the submitted work is original and does not contain excessive overlap with prior or contemporaneous publication elsewhere, and where the publication reports on cohorts, trials, or data that have been reported on before the facts need to be acknowledged and these other publications must be referenced; All original research work has been approved by the relevant bodies such as institutional review boards or ethics committees; All relevant conflicts of interest, financial or otherwise, that may affect the authors' ability to present data objectively, and relevant sources of funding of the research in question have been duly declared in the manuscript; All authors certify that they will submit the original source data to the editorial office upon request; The manuscript in its published form will be maintained on the servers of the journal as a valid publication only as long as all statements in these guidelines remain true; If any of the aforementioned statements ceases to be true, the authors have a duty to notify as soon as possible the Editor‐in‐Chief of the journal, so that the available information regarding the published article can be updated and/or the manuscript can be withdrawn.